A MODEL FOR PREPARING FUTURE GEOGRAPHY TEACHERS TO USE PROJECT TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2026)
In the article, the theoretical foundations of preparing future geography teachers to use project technologies in the educational process, the methodological system of preparing future geography teachers to use project technologies in the educational process, the use of project technologies in the educational process of future geography teachers the effectiveness of preparation for use has been studied. Also, the content of preparing future geography teachers to use project technologies in the educational process was analyzed.